2011
DOI: 10.1123/japa.19.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Can Improve Speed of Behavior in Older Drivers

Abstract: The main aim of this research was to study the effects of a specific exercise program on the speed of behavior of older adults during on-the-road driving. Twenty-six drivers (55-78 yr old) were randomly assigned to either an exercise group or a control group. The exercise program (3 sessions of 60 min/wk for 8 wk) incorporated tasks that induced the participants to respond quickly to challenging situations. On-the-road driving tasks (under single-and dual-task conditions) included measures of simple and choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
2
20
0
3
Order By: Relevance
“…Although based on a small sample, our results, which show a 22% reduction in driving simulator assessed demerit points following an exercise program, are consistent with other research which reported that healthy older adults over the age of 70 improved their driving performance by 37% following a 12-week exercise program including strength, flexibility, and coordination exercises (Marottoli et al, 2007). In other studies among older adults, training protocols combining physical and cognitive training led to driving related ability improvements, as quantified by on-road (Marmeleira et al 2011) and simulator based (Marmeleira et al, 2009) speed of behavior tasks. The improvements in driving scores among participants in the CR training in our study occurred despite the absence of any emphasis on cognitive or physical tasks specific to driving as included in these other studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although based on a small sample, our results, which show a 22% reduction in driving simulator assessed demerit points following an exercise program, are consistent with other research which reported that healthy older adults over the age of 70 improved their driving performance by 37% following a 12-week exercise program including strength, flexibility, and coordination exercises (Marottoli et al, 2007). In other studies among older adults, training protocols combining physical and cognitive training led to driving related ability improvements, as quantified by on-road (Marmeleira et al 2011) and simulator based (Marmeleira et al, 2009) speed of behavior tasks. The improvements in driving scores among participants in the CR training in our study occurred despite the absence of any emphasis on cognitive or physical tasks specific to driving as included in these other studies.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to being associated with improvements in cardiovascular fitness (Ades, 2001;Kavanagh et al, 2002;Leon et al, 2005), data suggest that participation in an exercise-centered cardiac rehabilitation (CR) may also relate to improvements in cognition performance (Gunstad et al, 2005;Stanek et al, 2011). Although physical exercise has been linked to improvements in abilities associated with driving performance in healthy adults (Filipe Marmeleira et al, 2011;Marmeleira et al, 2009;Marottoli et al, 2007), it was never explored whether physical exerciserelated enhancements in driving performance could be perceived among persons with CVD. The aim of the present study was to investigate the possible relationship between a 12 week CR program and changes in simulator-tested driving performance in adults with CVD.…”
Section: Introductionmentioning
confidence: 99%
“…In this view, it is reasonable to consider that the improvement of information processing speed has the potential to impact the general cognitive ability in older adults, leading to positive effects on their functional status, independence and quality of life [36,100]. This was already shown in the cognitive training literature [5], and recent studies have also reported positive effects of exercise programs on the information processing speed of older adults [84,85]. Future research using longitudinal designs is needed to examine which exercise characteristics could improve information processing speed in older adults and if this hypothetical improvement has a large impact on the individual's functional abilities.…”
Section: Implications For Research On the Effects Of Exercise On The mentioning
confidence: 91%
“…Efforts should be taken to extend this line of investigation and to examine if the effects of exercise that merge physical and cognitive stimulation might transfer to other tasks of daily living in older adults. As we have seen before, some studies have already provided a positive answer to this question, namely in the context of driving [84,85]. It is desirable that more research be conducted to examine the general effects of exercise interventions planned to stress not only physiological systems, but also perceptive and cognitive mechanisms.…”
Section: Implications For Research On the Effects Of Exercise On The mentioning
confidence: 99%
See 1 more Smart Citation